Is Natural Orifice Specimen Extraction Surgery Really Safe in Radical Surgery for Colorectal Cancer? - Liu, Gang; Shi, Lianghui; Wu, Zehui (Frontiers in Endocrinology, 2022)
Background The main feature of natural orifice specimen extraction (NOSE) is its avoidance of an auxiliary abdominal incision. The safety of NOSE remains controversial. This study aimed to investigate the early safety of transanal NOSE in the treatment of sigmoid colon and upper rectal cancer from the follow aspects: clinical and pathological characteristics, inflammatory and immune indicators and postoperative complications. Methods Data from 125 patients diagnosed with sigmoid colon, and upper rectal cancer by gastrointestinal surgery in the First Affiliated Hospital of Wannan Medical College from January 2017 to June 2020 were analyzed. Patients were assigned to two surgical groups: Conventional laparoscopic-assisted radical resection for CRC (CLA, 75cases) and laparoscopic-assisted radical resection for CRC with NOSE (La-NOSE, 50 cases). The following were compared: clinical and pathological characteristics; intraoperative, bacteriological, and oncological results; postoperative inflammation and immune response indexes. Bacteriological results were obtained by aerobic and anaerobic bacterial culture of peritoneal wash fluid and oncology results by cytological analysis of peritoneal wash liquid exudation. Inflammation indicators included postoperative C-reactive protein (CRP) and procalcitonin (PCT) trend reactions. The immune index was the level of postoperative T lymphocytes (CD3, CD4/CD8). All data were analyzed by using SPSS statistical version 18.0 for windows. Measurement data are presented as the means ± standard deviations, and two-group comparisons were performed using the t-test. Comparisons of count data were performed using the chi-square test. p <0.05 indicates that the difference was statistically significant. Results The bacterial culture positive rate was not significant in the La-NOSE group (15/50 vs 19/75) than in the CLA group. The exfoliative cytology (EC) rate of the peritoneal wash fluid was 0 in both groups.The La-NOSE group had a significantly higher postoperative day 2(POD2) CRP and PCT level than the CLA group. The POD2 CD3 and CD4/CD8 levels were higher in the La-NOSE group than in the CLA group. There was no significant difference in the incidence of postoperative complications between the two groups (La-NOSE group vs CLA group: 3/50 vs 6/75) (p>0.05). Conclusions Although the incidence of intra-abdominal contamination is high, it does not develop into a severe infectious disease, and does not lead to the implantation of free tumor cells into the abdominal cavity. Therefore, it is safe for the NOSE to treat colorectal cancer.